PENGARUH KEPUASAN KERJA, IKLIM ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN PT. KINDO RITEL PRIMA - Ni Kadek Berliana Yola Hindristina; I Wayan Sujana; Ni Nyoman Ari Novarini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
Organizational Citizenship Behavior (OCB) has an important role in increasing the effectiveness, efficiency and profit for the organization. This study aims to determine the effect of job satisfaction, organizational climate, organizational commitment, and organizational support on organizational citizenship behavior (OCB) among employees of PT. Kindo Ritel Prima. This research was conducted at PT. Kindo Ritel Prima using a sample of 85 employees. The sampling technique used was the census method. Data collection was carried out through interviews and questionnaires, with the data analysis technique used is multiple linear regression analysis processed using SPSS version 23 software. Based on the results of the analysis, this study shows that job satisfaction, organizational climate and organizational commitment have a positive and significant effect on organizational citizenship. behavior (OCB) to employees of PT. Kindo Ritel Prima